E-Worksheets Based on Ethno-Modeling and Tri-N to Improve Mathematical Critical Thinking Skills of Grade VII Students - Hani Handayani; Sri Adi Widodo; Irham Taufiq; Wahyu Hidayat; Usman Arifin (Journal of Instructional Mathematics, 2026)
Mathematical critical thinking remains an essential yet underdeveloped competency in 21st-century mathematics learning, particularly when instruction lacks meaningful cultural context. At SMP Pembangunan Piyungan, number-topic instruction predominantly emphasizes procedural over contextual and reflective thinking, signaling an urgent need for culturally-grounded, innovative learning media. This study examines the improvement trend in seventh-grade students' mathematical critical thinking ability through E-Worksheets integrating Ethno-Modeling—connecting mathematical concepts with Piyungan's local cultural context—and the Tri-N approach (Niteni, Nirokke, Nambahi), which systematically guides students through observing, imitating, and developing ideas. Employing a time-series design, data were collected via mathematical critical thinking tests administered at each intervention meeting and analyzed quantitatively by tracking average score trends over time. Results demonstrate a consistent upward trend, with average scores rising from 89.09 at the first meeting to 96.18 at the seventh—indicating that E-Worksheets grounded in local cultural contexts and structured Tri-N learning stages effectively foster students' mathematical critical thinking development. These findings position Ethno-Modeling-based E-Worksheets integrated with Tri-N as a promising alternative medium for meaningful and culturally responsive mathematics learning.